Higher Education Policies in Latin America During the 21st Century: Inclusion or Quality? - Chiroleu, Adriana (Education Policy Analysis Archives, 2012)
This paper is meant to analyze the conformation of the government agendas related to Higher Education and the policies thereby created in Argentina, Brazil and Venezuela, highlighting their differences and similarities and the renovation or ongoing policies which are discussed when referring to the ‘90s policies. In spite of the new winds of political changes that the region is going through, the option seems to remain the same: inclusion or quality? Two terms that are sometimes shown as to being antagonistic but which actually can coexist mutually.